2022
DOI: 10.1038/s41598-022-10390-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation is sufficient to release porcine sperm from immobilized oviduct glycans

Abstract: Fertilizing sperm are retained by adhesion to specific glycans on the epithelium of the oviduct forming a reservoir before sperm are released from the reservoir so fertilization can ensue. Capacitated sperm lose affinity for the oviduct epithelium but the components of capacitation that are important for sperm release are uncertain. One important correlate of capacitation is the development of hyperactivated motility. Hyperactivation is characterized by asymmetrical flagellar beating with high beat amplitude. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…There are many different compounds known to induce hyperactivation, including Ca 2+ ionophore A23187, progesterone, and CatSper activators like 4-aminopyridine and procaine (Schmidt and Kamp 2004;Sharif et al 2022). When Ca 2+ ionophore A23187 was used in a previous study (Schmidt and Kamp 2004), approximately 60% of the incubated sperm switched from non-hyperactive to hyperactive motility.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different compounds known to induce hyperactivation, including Ca 2+ ionophore A23187, progesterone, and CatSper activators like 4-aminopyridine and procaine (Schmidt and Kamp 2004;Sharif et al 2022). When Ca 2+ ionophore A23187 was used in a previous study (Schmidt and Kamp 2004), approximately 60% of the incubated sperm switched from non-hyperactive to hyperactive motility.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm was attached to these specific glycans, forming a reservoir of sperm at the oviduct. Progesterone (80 nM) induced sperm release from oviduct glycans within 30 min [31].…”
Section: Andrologiamentioning
confidence: 99%
“…Components of the UPS were shown to participate in capacitation events, such as degradation of protein kinase cAMP-dependent type I regulatory subunit alpha (PRKAR1) and A-kinase anchoring protein 3 (AKAP3) protein [ 39 , 40 , 41 ]; acrosomal remodeling, protein processing, and compartmentalization [ 42 , 43 , 44 ]; hyperactivation [ 41 , 45 ]; and spermadhesin de-aggregation from the sperm surface necessary for sperm detachment from the oviductal epithelium [ 46 ]. In an in vitro and ex vivo capacitation assay, the 26S proteasome is physiologically important for the detachment of spermatozoa from oviductal glycan beads and explants [ 47 , 48 ]. A recent computational study suggested the 26S proteasome to be one of two key regulators of mammalian sperm capacitation [ 49 ].…”
Section: Introductionmentioning
confidence: 99%